Method for producing olefin polymer

Purifying polymerization solvents with high silica zeolites addresses the issue of decreased catalyst activity in metallocene-based systems, allowing for efficient olefin polymer production by maintaining high polymerization activity.

JP7669783B2Active Publication Date: 2025-04-30TOSOH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021080146
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-05-11
Publication Date
2025-04-30
Estimated Expiration
2041-05-11

AI Technical Summary

Technical Problem

Existing methods for purifying recovered polymerization solvents are inadequate for use with high-activity metallocene-based catalysts, leading to decreased catalyst activity and inefficient olefin polymer production.

Method used

The use of a recovery polymerization solvent purified by catalytic treatment with high silica zeolites, specifically hydrogen cationic beta, ZSM-5, or Y zeolites, which effectively removes impurities and maintains catalyst activity during olefin polymerization.

Benefits of technology

This method enables efficient production of olefin polymers by maintaining high polymerization activity of metallocene-based catalysts, even when reusing solvents initially used with Ziegler-Natta catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669783000001
    Figure 0007669783000001
Patent Text Reader

Abstract

To provide a method for producing an olefinic polymer which shows almost no influence on olefinic polymerization activity of a metallocene catalyst and the like even if using a recovered polymerization solvent which has been used for olefinic slurry polymerization.SOLUTION: The present invention discloses a method for producing an olefinic polymer. In the presence of a metallocene catalyst, olefinic polymerization is performed which uses, as a polymerization solvent, the polymerization solvent that has been used in the olefinic polymerization reaction and then brought into contact with at least one high silica zeolite selected from the group consisting of hydrogen cationic beta zeolite, hydrogen cationic ZSM-5 zeolite and hydrogen cationic Y-type zeolite.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an olefin polymer, and more particularly to a method for producing an olefin polymer in the presence of a metallocene catalyst, in which a recovered polymerization solvent used in slurry polymerization of an olefin in the presence of a solid catalyst containing titanium, magnesium and a halogen is used. [Background technology]

[0002] The method of slurry polymerization of olefins in a polymerization solvent using a polymerization catalyst, such as a so-called Ziegler-Natta catalyst or a metallocene catalyst, which is a solid catalyst containing titanium, magnesium, and halogen, is widely used. When performing slurry polymerization industrially, it is common to recover the solvent after separating the produced polymer and reuse it for polymerization in order to reduce costs and waste. The recovered polymerization solvent from which the produced polymer is separated contains impurities such as residual raw materials, by-products, and catalyst decomposition products of the polymerization reaction, and there is concern that these may become substances that have various adverse effects on the polymerization reaction, so it cannot be used as is except in some cases.

[0003] In other words, purification of polymerization solvents is important for controlling polymerization reactions, and polymer manufacturers are making efforts to minimize the impact on polymerization reactions by making full use of their own purification technologies. In recent years, the amount of catalyst used has been reduced due to the high activity of polymerization catalysts, and the co-production (swing operation) of metallocene catalysts and conventional Ziegler-Natta catalysts for the production of higher value-added polymers has become more common. However, solvents recovered using conventional purification methods tend to reduce the performance of metallocene catalysts, which have low tolerance to impurities, and the development of a solvent recovery method that allows for more advanced purification has been desired.

[0004] The use of zeolites has been proposed for the purpose of removing water or alkyl halides contained in a solvent and purifying it. For example, a method has been proposed in which a solvent recovered from a slurry produced by polymerization of α-olefins using a Ziegler or Wacker catalyst is treated with a synthetic zeolite having pores of 8 Å or more, preferably Molecular Sieves 10X or Molecular Sieves 13X (see, for example, Patent Document 1). Another method has been proposed in which sodium cations of zeolite are exchanged with transition metal ions such as iron to obtain a high solvent purification effect (see, for example, Patent Document 2). Furthermore, a method has been proposed in which a solvent separated from a slurry produced by slurry polymerization of α-olefins in the presence of a Ziegler-Natta catalyst is contact-treated with a combination of two types of zeolites having different pore sizes, preferably Molecular Sieves 10X and Molecular Sieves 3A, to remove trace amounts of polymerization-inhibiting impurities that could not be removed in the past (see, for example, Patent Document 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 57-56924 [Patent Document 2] Special Publication No. 1-58202 [Patent Document 3] Special Publication No. 6-17405 Summary of the Invention [Problem to be solved by the invention]

[0006] However, all of the proposals in Patent Documents 1 to 3 involve reusing the purified solvent in slurry polymerization of a Ziegler-Natta catalyst, and no consideration is given to the applicability of such methods to highly active and precise polymerization catalysts such as metallocene catalysts. According to the inventors' studies, when such methods are applied to metallocene catalysts, a decrease in activity, etc., is observed.

[0007] Therefore, there has been a demand for an efficient method for producing olefin polymers that uses recovered polymerization solvent that is not affected by influential substances and impurities, even in swing operation of olefin polymers produced by conventional Ziegler-Natta catalysts and olefin polymers produced by high-performance catalysts, such as metallocene catalysts, which enable highly active and precise polymerization. [Means for solving the problem]

[0008] Therefore, the present inventors have discovered that, during olefin polymerization using a metallocene catalyst, efficient production of olefin polymers is possible by purifying the recovered polymerization solvent using a specific hydrogen cation type high silica zeolite, and have thus completed the present invention.

[0009] That is, the present invention relates to a method for producing an olefin polymer, characterized in that, when polymerizing an olefin in the presence of a metallocene catalyst, a recovered polymerization solvent obtained by contact-treating the polymerization solvent after an olefin polymerization reaction with at least one high silica zeolite selected from the group consisting of hydrogen cation type beta zeolite, hydrogen cation type ZSM-5 zeolite and hydrogen cation type Y zeolite is used as the polymerization solvent.

[0010] The present invention will be described in detail below.

[0011] The method for producing an olefin polymer of the present invention uses a recovered polymerization solvent that has been contact-treated with a high-silica zeolite selected from the group consisting of hydrogen cation-type beta zeolite, hydrogen cation-type ZSM-5 zeolite, and hydrogen cation-type Y zeolite. Here, zeolite is a general term for crystalline aluminosilicates, and has a chemical composition represented by the general formula Me2 / XO·Al2O3·mSiO2·nH2O (wherein Me represents an alkali metal or alkaline earth metal, and X represents the atomic valence of Me), and has a unique crystal structure that can be identified by X-ray diffraction. Among these zeolites, high-silica zeolites belonging to the hydrogen cation type beta zeolite, hydrogen cation type ZSM-5 zeolite, and hydrogen cation type Y zeolite, in particular hydrogen cation type Y zeolite, exhibit excellent performance in purifying the recovered polymerization solvent, while high-silica zeolites other than the hydrogen cation type, beta zeolite, ZSM-5 zeolite, and Y zeolite, do not sufficiently purify the recovered polymerization solvent.

[0012] There is no limitation on the SiO2 / Al2O3 (molar ratio) of the high-silica zeolite, and among them, those with SiO2 / Al2O3 = 5 to 40 are preferred because they exhibit particularly excellent solvent purification capabilities, and those with SiO2 / Al2O3 = 5 to 30, 5 to 20, and even more preferably 5 to 10. It is generally known that the higher the SiO2 / Al2O3 molar ratio, the higher the acid strength of the high-silica zeolite. However, surprisingly, among high-silica zeolites, those with a relatively low SiO2 / Al2O3 molar ratio exhibit excellent recovered solvent purification capabilities.

[0013] The high-silica zeolite in the present invention may be a high-silica zeolite in which a part of the hydrogen cations has been replaced with transition metal ions for the purpose of imparting impurity removal ability, high durability, and easy regeneration, and can be prepared, for example, by the method described in JP-B-1-58202. The exchange rate differs depending on the type of polymerization solvent recovered, but in general it is preferably 40% or less of the total hydrogen cation amount, particularly 1 to 20%, and further preferably 1 to 10%.

[0014] The form of the high-silica zeolite in the present invention is not particularly limited, and general forms such as powder, granules, pellets, etc. can be used, and from the viewpoint of operation, granules or pellets are particularly suitable, and from the viewpoint of purification ability, powders with a large specific surface area are superior. When the high-silica zeolite is made into a pellet form, it may further contain a binder such as silica, alumina, silica-alumina, clay, etc.

[0015] Such high silica zeolite can be obtained by a generally known method. It may also be a commercially available product, for example, hydrogen cation type Y-type high silica zeolite (product name) HSZ-330HUD1A (manufactured by Tosoh Corporation), hydrogen cation type beta-type high silica zeolite (product name) HSZ-931HOD1A (manufactured by Tosoh Corporation), hydrogen cation type ZSM-5-type high silica zeolite (product name) HSZ-822HOD1A (manufactured by Tosoh Corporation), (product name) HSZ-840HOD1A (manufactured by Tosoh Corporation), etc.

[0016] High-silica zeolite can remove and purify polymerization inhibitors and impurities by contacting with the polymerization solvent recovered after the polymerization reaction is completed, and in this case, it is preferable to subject the high-silica zeolite to contact treatment at the final stage of the purification of the recovered polymerization solvent after the usual purification processes of filtering, distilling, removing water, etc. This shows that high-silica zeolite can remove inhibitors and impurities that cannot be removed by usual purification processes.

[0017] The recovered polymerization solvent in the present invention may be any polymerization solvent recovered from a polymerization reaction, and is particularly suitable for use in a polymerization solvent containing by-products from side reactions and metal-containing substances derived from catalysts. An example of such a polymerization reaction is slurry polymerization in which olefins are polymerized in the presence of a Ziegler-Natta catalyst.

[0018] The Ziegler-Natta catalyst in this case may be a solid catalyst containing titanium, magnesium and a halogen, which may be used in olefin polymerization in combination with an organoaluminum compound for activating the catalyst and / or removing impurities. More specifically, the solid catalyst is a composite solid formed by stepwise or primary contact of a magnesium compound with a halogen-containing titanium compound or an adduct of the compound with an electron donor, and many preparation methods of such catalysts have been developed with various ingenuity. However, the present invention is not particularly limited and can be applied to the case where various known catalysts are used. Specifically, the methods disclosed in JP-B-46-34092, JP-A-54-41985, JP-A-55-729, JP-A-55-13709, JP-A-57-12006, JP-A-57-141409, and JP-B-4-22163 may be mentioned.

[0019] Examples of the olefin include α-olefins such as ethylene, propylene, butene-1, hexene-1, and octene-1.

[0020] The solvent used in the slurry polymerization is not particularly limited as long as it is a hydrocarbon solvent. Examples of the solvent include aliphatic hydrocarbons such as butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene; aliphatic hydrocarbons having a cyclic structure such as cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, and xylene.

[0021] In the present invention, the recovered polymerization solvent used in contact with the high-silica zeolite is preferably subjected to filtration, distillation, water removal, etc. in advance in order to improve the efficiency of purification. In particular, in the case of slurry polymerization in which olefins are polymerized in the presence of a Ziegler-Natta catalyst, it is preferable that the solvent has been subjected to the treatments shown in 1) to 4) below. 1) After recovering and removing the produced polymer, the solvent is hydrolyzed and the organic layer is separated and recovered. In some cases, the pH of the aqueous layer of the hydrolyzed solution is adjusted. 2) The organic layer recovered in 1) is steam distilled, and the organic layer is separated from the effluent. 3) The organic layer separated in 2) is subjected to simple distillation. 4) The recovered solvent obtained by simple distillation in 3) is subjected to contact treatment with molecular sieves 3A or 4A for the purpose of dehydrating it.

[0022] The conditions for contacting the recovered polymerization solvent, the pretreated recovered polymerization solvent, and the high-silica zeolite are not particularly limited. Among them, since the high-silica zeolite is hydrophobic but also exhibits water removal ability, it is preferable to reduce the water content by dehydration before treatment. Specifically, it is preferable to make the water content measured by the Karl Fischer method 20 ppm or less. The treatment temperature can be set arbitrarily in the range of -10°C to 150°C, taking into consideration the freezing point, boiling point, and viscosity of the recovered polymerization solvent to be treated. Basically, a higher temperature gives a better result, but sufficient performance can usually be obtained by treating at a temperature in the range of 25°C to 50°C. In addition, in the contact treatment of the recovered polymerization solvent and the high-silica zeolite, care should be taken to prevent the high-silica zeolite from entraining air bubbles. A method of statically immersing the high-silica zeolite in the recovered polymerization solvent may be used, but in consideration of industrial use, it is preferable to pass the recovered polymerization solvent through a column packed with high-silica zeolite so that it becomes an upflow. The contact time can be adjusted by using the column diameter, packing length, and flow rate as parameters. The contact time depends on the amount of impurities remaining in the recovered solvent, but for example, when contacting 5 L of solvent with 10 g of high-silica zeolite, the contact time can be adjusted arbitrarily within the range of 1 second to 24 hours.

[0023] Furthermore, high-silica zeolite can be restored to its original performance and reused by periodically or when its activity has significantly decreased, by calcining it at a temperature in the range of 200°C to 700°C under a flow of inert gas such as nitrogen.

[0024] The recovered polymerization solvent purified by high-silica zeolite can be reused as a polymerization solvent in a polymerization reaction again without affecting the production of a polymer. In the present invention, the recovered polymerization solvent is used as a polymerization solvent in carrying out slurry polymerization of an olefin in the presence of a metallocene catalyst, which is known as an olefin polymerization catalyst having particularly excellent polymerization activity and suitable for precision polymerization.

[0025] There are no particular limitations on the polymerization of olefins by metallocene catalysts using the recovered polymerization solvent in this case, and olefin polymerization is carried out using a catalyst system in which a metallocene complex is combined with a cocatalyst such as methylaluminoxane or triphenylcarbenium tetrakispentafluorophenylborate-triisobutylaluminum.

[0026] The metallocene complex in this case has a general formula MR1R2R3R4 (wherein M represents a transition metal element, at least one of R1, R2, R3, and R4 is an organic group having a cycloalkadienyl skeleton, and the remaining groups independently represent an alkyl group, an alkoxy group, an aryloxy group, an alkylsilyl group, an alkylamide group, an alkylimide group, an alkylamino group, an alkylimino group, or a halogen atom. When two or more of R1, R2, R3, and R4 are organic groups having a cycloalkadienyl skeleton, at least two of the organic groups having a cycloalkadienyl skeleton may be bridged by carbon, silicon, or germanium.) The metallocene complex is known as a main component of an olefin polymerization catalyst, and M is specifically titanium, zirconium, hafnium, chromium, vanadium, manganese, iron, cobalt, nickel, or palladium, and preferably titanium, zirconium, chromium, iron, or nickel. A preferred transition metal compound is a metallocene compound with one or two ligands having a cycloalkadienyl skeleton. Examples of the ligand having a cycloalkadienyl skeleton include alkyl-substituted cyclopentadienyl groups such as cyclopentadienyl, methylcyclopentadienyl, ethylcyclopentadienyl, butylcyclopentadienyl, dimethylcyclopentadienyl, and pentamethylcyclopentadienyl, indenyl, and fluorenyl groups, and the cycloalkadienyl groups may be crosslinked with divalent substituted alkylene groups, substituted silylene groups, or the like.

[0027] The ligand other than the ligand having a cycloalkadienyl skeleton is a hydrocarbon group having 1 to 20 carbon atoms, an alkoxy group, an aryloxy group, an alkylsilyl group, an amino group, an imino group, a halogen atom, or a hydrogen atom. Examples of the hydrocarbon group having 1 to 20 carbon atoms include an alkyl group, a cycloalkyl group, an aryl group, and an aralkyl group. Specifically, examples of the alkyl group include a methyl group, an ethyl group, a propyl group, an isopropyl group, and a butyl group. Examples of the cycloalkyl group include a cyclopentyl group and a cyclohexyl group. Examples of the aryl group include a phenyl group and a tolyl group. Examples of the aralkyl group include a benzyl group. Examples of the alkoxy group include a methoxy group, an ethoxy group, and a butoxy group. Examples of the aryloxy group include a phenoxy group. These groups may be substituted with a halogen atom. Examples of the alkylsilyl group include a trimethylsilyl group and a triethylsilyl group. Examples of the halogen include fluorine, chlorine, bromine, and iodine.

[0028] Specific examples of transition metal compounds in which M is zirconium and which contain a ligand having a cycloalkadienyl skeleton include bis(cyclopentadienyl)zirconium monochloride monohydride, bis(cyclopentadienyl)zirconium monobromide monohydride, bis(cyclopentadienyl)methylzirconium hydride, bis(cyclopentadienyl)ethylzirconium hydride, bis(cyclopentadienyl)phenylzirconium hydride, and bis(cyclopentadienyl)benzylzirconium hydride. hydride, bis(cyclopentadienyl)neopentylzirconium hydride, bis(methylcyclopentadienyl)zirconium monochloride hydride, bis(indenyl)zirconium monochloride hydride, bis(cyclopentadienyl)zirconium dichloride, bis(cyclopentadienyl)zirconium dibromide, bis(cyclopentadienyl)methylzirconium monochloride, bis(cyclopentadienyl)ethylzirconium monochloride, bis(cyclopentadienyl)zirconium dichloride Bis(cyclopentadienyl)cyclohexylzirconium monochloride, bis(cyclopentadienyl)phenylzirconium monochloride, bis(cyclopentadienyl)benzylzirconium monochloride, bis(methylcyclopentadienyl)zirconium dichloride, bis(dimethylcyclopentadienyl)zirconium dichloride, bis(n-butylcyclopentadienyl)zirconium dichloride, bis(indenyl)zirconium dichloride, bis(indenyl)zirconium dibromide, bis(cyclopentadienyl) cyclopentadienyl)zirconium dimethyl, bis(cyclopentadienyl)zirconium diphenyl, bis(cyclopentadienyl)zirconium dibenzyl, bis(cyclopentadienyl)zirconium monomethoxy monochloride, bis(cyclopentadienyl)zirconium monoethoxy monochloride, bis(methylcyclopentadienyl)zirconium monoethoxy monochloride, bis(cyclopentadienyl)zirconium monophenoxy monochloride, and bis(fluorenyl)zirconium dichloride.

[0029] Specific examples of transition metal compounds in which M is zirconium and at least two ligands having a cycloalkadienyl skeleton are bonded via an alkylene group such as ethylene or propylene, a substituted alkylene group such as isopropylidene or diphenylmethylene, a silylene group, a substituted silylene group such as dimethylsilylene, or a substituted germanediyl group such as dimethylgermanediyl or diphenylgermanediyl include ethylenebis(indenyl)dimethylzirconium, ethylenebis(indenyl)dimethylzirconium, and ethylenebis(indenyl)dimethylzirconium. bis(indenyl)diethylzirconium, ethylene bis(indenyl)diphenylzirconium, ethylene bis(indenyl)methylzirconium monochloride, ethylene bis(indenyl)ethylzirconium monochloride, ethylene bis(indenyl)methylzirconium monobromide, ethylene bis(indenyl)zirconium dichloride, ethylene bis(indenyl)zirconium bromide, ethylene bis(4,5,6-tetrahydro-1-indenyl)zirconium dichloride, dimethylsilylene bis(indenyl)zirconium dichloride Chloride, diphenylsilylene bis(indenyl)zirconium dichloride, dimethylsilylene bis(2-methyl-4-phenylindenyl)zirconium dichloride, dimethylsilylene bis(2-methyl-4-(1-naphthyl)indenyl)zirconium dichloride, dimethylgermanediylbis(indenyl)zirconium dichloride, diphenylgermanediylbis(indenyl)zirconium dichloride, dimethylgermanediylbis(2-methyl-4-phenylindenyl)zirconium dichloride, dimethylgermanediylbis(2-methyl-4-phenylindenyl)zirconium dichloride, dimethylgermanediylbis(indenyl)zirconium dichloride Diylbis(2-methyl-4-(1-naphthyl)indenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(fluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,7-dimethylfluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-dimethylfluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2-dimethylaminofluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-dimethylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2-diisopropylaminofluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2-diisopropylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(4-di Methylaminofluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(4-dimethylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(4-diisopropylaminofluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(4-diisopropylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,7-bisdimethylaminofluorenyl) Zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-bisdimethylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,7-bisdiisopropylaminofluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-bisdiisopropylaminofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2-methoxyfluorenyl)zirconium di Chloride, diphenylmethylene(cyclopentadienyl)(2-methoxynofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(4-methoxyfluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(4-methoxynofluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,7-dimethoxyfluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,7-Dimethoxyfluorenyl)zirconium dimethyl, diphenylmethylene(cyclopentadienyl)(2,3,7-trimethoxyfluorenyl)zirconium dichloride, diphenylmethylene(cyclopentadienyl)(2,3,7-trimethoxyfluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(fluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(fluorenyl)zirconium dimethyl, diphenylsilanediyl (Cyclopentadienyl)(2,7-dimethylfluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-dimethylfluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2-dimethylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-dimethylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2-diisopropylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-dimethylaminofluorenyl)zirconium dimethyl nyl)(2-diisopropylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(4-dimethylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-dimethylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(4-diisopropylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-diisopropylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2,7-bisdimethylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bisdimethylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2,7-bisdiisopropylaminofluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-bisdiisopropylaminofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2-methoxyfluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2-methoxynofluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(4-methoxyfluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(4-methoxyfluorenyl)zirconium dichloride Examples of the zirconium complex include diphenylsilanediyl(cyclopentadienyl)(2,7-dimethoxyfluorenyl)zirconium dichloride, diphenylsilanediyl(cyclopentadienyl)(2,7-dimethoxyfluorenyl)zirconium dimethyl, diphenylsilanediyl(cyclopentadienyl)(2,3,7-trimethoxyfluorenyl)zirconium dichloride, and diphenylsilanediyl(cyclopentadienyl)(2,3,7-trimethoxyfluorenyl)zirconium dimethyl, and may be racemic, meso or mixtures thereof. In addition, examples of the zirconium complex include complexes in which the zirconium is replaced with titanium or hafnium.

[0030] When preparing a solid catalyst in advance for slurry polymerization, only one of these complexes may be supported and used, or two or more of them may be supported and used for the purpose of adjusting the molecular weight distribution, etc.

[0031] Examples of the carrier used in advance when preparing the solid catalyst include inorganic solids such as magnesium chloride, SiO2, and alumina, and organic solids such as polyethylene, polypropylene, and polystyrene. In addition, examples of the solid carrier having a cocatalyst function include SiO2 and alumina treated with methylaluminoxane, solid methylaluminoxane described in WO2010 / 055562, WO2013 / 055652, and Japanese Patent No. 6259549, and treated carriers of clay minerals described in JP-A-2015-93909, JP-A-2016-175960, JP-A-2018-145402, and JP-A-2019-16743.

[0032] The method for producing an olefin polymer of the present invention uses a recovered polymerization solvent and a catalyst supported on a metallocene complex and a cocatalyst support to polymerize an olefin. The olefins used in the polymerization include α-olefins such as ethylene, propylene, butene-1, pentene-1, hexene-1, octene-1, decene-1, hexadecene-1, octadecene-1, and eicosene-1; halogen-substituted olefins such as bisfluoroethylene, trifluoroethylene, tetrafluoroethylene, and hexafluoropropene; and cyclic olefins such as cyclopentene, cyclohexene, and norbornene, and these can be used alone or in combination.

[0033] The olefin production method of the present invention may be either continuous polymerization or batch polymerization, and even if a recovered polymerization solvent is used, favorable performance is exhibited, and the effect of hydrogen as a molecular weight regulator can be maintained at a high level. In addition, there are no limitations on the polymerization conditions such as the polymerization temperature, polymerization time, polymerization pressure, and monomer concentration, and it is preferable to carry out the polymerization at a polymerization temperature of 30 to 90°C, for a polymerization time of 10 seconds to 20 hours, and at a polymerization pressure of normal pressure to 100 MPa. In addition, the ethylene polymer obtained after the polymerization is separated and recovered from the polymerization solvent by a conventionally known method, and can be obtained by drying. Effect of the Invention

[0034] According to the present invention, even when a polymerization solvent used in olefin polymerization using a Ziegler-Natta catalyst is reused for olefin polymerization using a metallocene catalyst, it is possible to efficiently produce olefins without causing a decrease in polymerization activity. EXAMPLES

[0035] The present invention will be described in more detail below by showing examples, but the present invention is not limited to these examples.

[0036] Unless otherwise specified, the reagents used were either commercially available or synthesized according to known methods.

[0037] Reference example 1 A Ziegler-Natta catalyst was prepared according to the method described in JP-B-4-22163, and ethylene was polymerized to prepare a polymerization solvent after polymerization.

[0038] (1) Preparation of Ziegler-Natta catalyst 70g (0.94mol) of butanol was placed in a 1.6L autoclave equipped with a stirrer, to which 0.55g of iodine, 11g (0.45mol) of metallic magnesium powder, and 61g (0.18mol) of titanium tetrabutoxide were added, followed by 450ml of dry hexane. The mixture was then heated to 80°C and stirred for one hour under a nitrogen seal while removing the generated hydrogen gas. The mixture was then heated to 120°C and reacted for one hour to obtain a solution containing magnesium and titanium.

[0039] A solution containing magnesium and titanium in an amount equivalent to 0.048 moles of magnesium atom was added to a flask with an internal volume of 500 ml, and the temperature was raised to 45°C. A hexane solution of tri-i-butylaluminum (0.048 mol) was added over 1 hour. After all was added, the mixture was stirred at 60°C for 1 hour. Next, 2.8 ml of methylhydrogenpolysiloxane (viscosity 30 centistokes at 25°C, silicon 0.048 gram atom) was added and reacted under reflux for 1 hour. After cooling to 45°C, 82 ml of a 50% hexane solution of i-butylaluminum dichloride was added over 2 hours. After all was added, the mixture was stirred at 70°C for 1 hour. Hexane was added to the product, and washing was performed 15 times by decantation. A slurry of solid catalyst (containing 9.5 g of solid catalyst), which is a Ziegler-Natta catalyst containing titanium, magnesium, and halogen, was obtained, suspended in hexane. A portion was sampled and subjected to elemental analysis, and the dry solid contained 9.0 wt% Ti.

[0040] (2) Ethylene polymerization The inside of a 20 L stainless steel autoclave equipped with a stirrer, thermometer, and pressure gauge was thoroughly replaced with nitrogen, 12 L of hexane was charged, and the inside temperature was adjusted to 80°C. Then, 2.3 g (12 mmol) of tri-i-butylaluminum and the slurry containing the solid catalyst obtained in (1) above were added in sequence. After adjusting the inside pressure of the autoclave to 0.1 MPa with nitrogen, hydrogen was added to make it 0.5 MPa, and then polymerization was carried out for 1.5 hours while continuously adding ethylene so that the inside pressure of the autoclave became 1.1 MPa. After the polymerization was completed, the mixture was cooled, and the slurry containing polyethylene was taken out and filtered to remove solids, and hexane after the polymerization reaction was obtained.

[0041] (3) Pretreatment of polymerization solvent The recovered polymerization solvent containing impurities obtained in (2) was hydrolyzed by contact with water, and the organic layer was recovered by liquid separation. Next, high boiling point impurities were removed by steam distillation. The distilled liquid was separated to obtain an organic layer, which was then subjected to simple distillation under a nitrogen atmosphere. Further, a dehydration treatment was performed using a molecular sieve 3A to obtain hexane (hereinafter, sometimes referred to as crude hexane), which is the recovered polymerization solvent to be used in the purification treatment study of the present invention. The water content in the crude hexane was measured by the Karl Fischer method and found to be 10 ppm. When the crude hexane was analyzed by gas chromatography, peaks other than hexane were observed, confirming the presence of impurities.

[0042] Reference example 2 (1) Preparation of organically modified clay In a 1L glass flask equipped with a stirrer and a thermometer, 300 ml of Ekinen F-3 (manufactured by Japan Alcohol Sales Co., Ltd.) and 300 ml of distilled water were placed, 15.0 g of concentrated hydrochloric acid and 64.2 g (120 mmol) of Armin M20 (dioleylmethylamine, manufactured by Lion Corporation) were added, and the mixture was heated to 45°C to disperse 100 g of synthetic hectorite ((trade name) Laponite RDS, manufactured by BYK Japan Co., Ltd.), and then the mixture was heated to 60°C and stirred for 1 hour while maintaining the temperature. After filtering the slurry, it was washed twice with 600 ml of water at 60°C and dried in a dryer at 85°C for 12 hours to obtain 160 g of organically modified clay. This organically modified clay was pulverized by a jet mill to a median diameter of 15 μm.

[0043] (2) Preparation of metallocene catalyst After replacing the air in a 300 ml flask equipped with a stirrer, thermometer and reflux condenser with nitrogen, 25.0 g of the organically modified clay obtained in (1) and 108 ml of hexane were added, followed by 0.687 g of diphenylmethylene(cyclopentadienyl)(2-(dimethylamino)-9-fluorenyl)hafnium dichloride and 142 ml of a hexane solution of tri-i-butylaluminum diluted to 20 wt% (manufactured by Tosoh Finechem Co., Ltd.) and stirring for 3 hours at 60°C. After cooling to 45°C, the supernatant was removed and washed twice with 200 ml of hexane, and 200 ml of hexane was added to obtain a suspension of a metallocene catalyst (solid weight content: 12 wt%).

[0044] Example 1 In a 5L flask equipped with a stirrer, 5L (3350g) of the crude hexane obtained in Reference Example 1 was introduced under a nitrogen atmosphere, and 3.0g of pellet-shaped hydrogen cation type Y-type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-330HUD1A; SiO2 / Al2O3 molar ratio 6, alumina binder) was added. After that, the mixture was left at room temperature for 24 hours while stirring to obtain hexane (1), which is a purified recovered polymerization solvent. The water content of the purified hexane (1) was reduced to 5ppm. In addition, the high silica zeolite was slightly yellowish. As a result of analysis by gas chromatography, no peaks other than hexane were observed.

[0045] The inside of a 2L stainless steel autoclave equipped with a stirrer, a thermometer, and a pressure gauge was fully replaced with nitrogen, 1.2L of purified hexane (1) was charged, and the inside temperature was adjusted to 60°C. Then, 0.65g (0.66mmol) of a 20wt% tri-i-butylaluminum solution diluted with hexane and a suspension containing 24mg of the metallocene catalyst obtained in Reference Example 2 were added in sequence. Polymerization was carried out for 90 minutes while continuously adding ethylene so that the internal pressure of the autoclave became 0.87MPa. After the polymerization was completed, the mixture was cooled, and the polyethylene-containing slurry was taken out and filtered to recover the polyethylene. When the weight was measured after drying, 87g of polyethylene was obtained. The polymerization activity at that time was 3625g / g-catalyst, which was a high polymerization activity. The evaluation results are shown in Table 1.

[0046] Example 2 A chromatographic column with a diameter of 2 cm was packed with pellet-shaped hydrogen cation type Y-type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-330HUD1A, SiO2 / Al2O3 molar ratio 6, alumina binder) to a height of 20 cm, and nitrogen replacement was performed. The packing density of the high silica zeolite at this time was 0.465 g / cm 3 In this column, crude hexane was passed through the bottom in an upflow manner under a nitrogen atmosphere, and the residence time was set to 120 seconds to obtain purified hexane (2). The amount of liquid passed through was 5 L. Analysis by gas chromatography showed that no peaks other than hexane were observed.

[0047] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (2) was used. After drying, the weight was measured to obtain 86 g of polyethylene. The polymerization activity was 3583 g / g-catalyst, which was a high polymerization activity. The evaluation results are shown in Table 1.

[0048] Example 3 Except for setting the residence time of the crude hexane to 30 seconds, the procedure of Example 2 was repeated to obtain purified hexane (3). As a result of analysis by gas chromatography, no peaks other than those of hexane were observed.

[0049] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (3) was used. After drying, the weight was measured to obtain 84 g of polyethylene. The polymerization activity was as high as 3500 g / g-catalyst. The evaluation results are shown in Table 1.

[0050] Example 4 Except for setting the residence time of the crude hexane to 10 seconds, the procedure of Example 2 was repeated to obtain purified hexane (4). As a result of analysis by gas chromatography, no peaks other than those of hexane were observed.

[0051] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (4) was used. After drying, the weight was measured to obtain 70 g of polyethylene. The polymerization activity was 2916 g / g-catalyst, which was a high polymerization activity. The evaluation results are shown in Table 1.

[0052] Example 5 A purified hexane (5) was obtained in the same manner as in Example 4, except that the column part was heated to 45° C. As a result of analysis by gas chromatography, no peaks other than those of hexane were observed.

[0053] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (5) was used. After drying, the weight was measured to obtain 78 g of polyethylene. The polymerization activity was 3250 g / g-catalyst, which was a high polymerization activity. The evaluation results are shown in Table 1.

[0054] Example 6 A purified hexane (6) was obtained in the same manner as in Example 1, except that the high silica zeolite was a pellet-shaped beta-type high silica zeolite having hydrogen cations (manufactured by Tosoh Corporation, (product name) HSZ-931HOD1A, SiO2 / Al2O3 molar ratio 27, alumina binder). The water content of the purified hexane (6) was measured, and found to be reduced to 6.5 ppm. Analysis by gas chromatography showed that no peaks other than those of hexane were observed.

[0055] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (6) was used. After drying, the weight was measured to obtain 80 g of polyethylene. The polymerization activity was 3333 g / g-catalyst, indicating high polymerization activity. The evaluation results are shown in Table 1.

[0056] Example 7 A purified hexane (7) was obtained in the same manner as in Example 1, except that the high silica zeolite was a pellet-shaped hydrogen cation type ZSM-5 type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-822HOD1A, SiO2 / Al2O3 molar ratio 23, alumina binder). The water content of the purified hexane (7) was measured, and it was found to have decreased to 7.4 ppm. As a result of analysis by gas chromatography, no peaks other than those of hexane were observed.

[0057] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (7) was used. After drying, the weight was measured to obtain 76 g of polyethylene. The polymerization activity was 3166 g / g-catalyst, indicating high polymerization activity. The evaluation results are shown in Table 1.

[0058] Example 8 A purified hexane (8) was obtained in the same manner as in Example 1, except that the high silica zeolite was a pellet-shaped hydrogen cation type ZSM-5 type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-840HOD1A, SiO2 / Al2O3 molar ratio 40, alumina binder). The water content of the purified hexane (8) was measured, and found to be slightly decreased to 8.1 ppm. Analysis by gas chromatography showed that no peaks other than those of hexane were observed.

[0059] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (8) was used. After drying, the weight was measured to obtain 68 g of polyethylene. The polymerization activity was 2833 g / g-catalyst, indicating high polymerization activity. The evaluation results are shown in Table 1.

[0060] Example 9 A purified hexane (9) was obtained in the same manner as in Example 4, except that a pellet-shaped hydrogen cation type Y-type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-330HUD1C, SiO2 / Al2O3 molar ratio 6, clay binder) was used. As a result of analysis by gas chromatography, no peaks other than hexane were observed.

[0061] Ethylene polymerization was carried out in the same manner as in Example 1, except that purified hexane (9) was used. After drying, the weight was measured to obtain 90 g of polyethylene. The polymerization activity was 3750 g / g-catalyst, which was a high polymerization activity. The evaluation results are shown in Table 1.

[0062] Comparative Example 1 (2) Polymerization of ethylene Ethylene polymerization was carried out in the same manner as in Example 1, except that crude hexane was used as is. After drying, the weight was measured to obtain 30 g of polyethylene. The polymerization activity was low, at 1250 g / g-catalyst. The evaluation results are shown in Table 1.

[0063] Comparative Example 2 Hexane was treated in the same manner as in Example 1, except that 10 g of zeolite (manufactured by Tosoh Corporation, product name Zeolum F-9) was used instead of high silica zeolite. The water content of the hexane treated with Zeolum was reduced to 5 ppm. Analysis by gas chromatography revealed peaks other than hexane.

[0064] Ethylene polymerization was carried out in the same manner as in Example 1, except that treated hexane was used. After drying, the weight was measured, and 38 g of polyethylene was obtained. The polymerization activity was low, at 1583 g / g-catalyst. The evaluation results are shown in Table 1.

[0065] Comparative Example 3 Hexane was treated in the same manner as in Example 1, except that instead of high silica zeolite, molecular sieves 10X (MS10X, Fujifilm Wako Pure Chemical Industries, Ltd.) and molecular sieves 3A (MS3A, Fujifilm Wako Pure Chemical Industries, Ltd.) that had been washed with water and dried were used and contacted in that order. The water content of the hexane treated with the molecular sieves here was reduced to 3 ppm. Analysis by gas chromatography revealed peaks other than hexane.

[0066] Ethylene polymerization was carried out in the same manner as in Example 1, except that treated hexane was used. After drying, the weight was measured, and 35 g of polyethylene was obtained. The polymerization activity was low, at 1458 g / g-catalyst. The evaluation results are shown in Table 1.

[0067] Comparative Example 4 Hexane was treated in the same manner as in Example 1, except that pellet-shaped sodium cation-type Y-type high silica zeolite (manufactured by Tosoh Corporation, (product name) HSZ-320NAD1C, SiO2 / Al2O3 molar ratio 5.5, clay binder) was used. The moisture content of the treated hexane was measured, and it was found to have decreased to 7 ppm. Analysis by gas chromatography revealed peaks other than hexane.

[0068] Ethylene polymerization was carried out in the same manner as in Example 1, except that treated hexane was used. After drying, the weight was measured, and 37 g of polyethylene was obtained. The polymerization activity was low, at 1541 g / g-catalyst. The evaluation results are shown in Table 1.

[0069] [Table 1] [Industrial Applicability]

[0070] According to the present invention, even when a polymerization solvent used in olefin polymerization using a Ziegler-Natta catalyst is reused for olefin polymerization using a metallocene catalyst, it is possible to efficiently produce olefin polymerization without causing a decrease in polymerization activity, and the present invention has extremely high industrial applicability.

Claims

1. A method for producing an olefin polymer, comprising the steps of: polymerizing an olefin in the presence of a metallocene catalyst; and using, as a polymerization solvent, a polymerization solvent obtained by contact-treating a polymerization solvent after an olefin polymerization reaction with at least one high silica zeolite selected from the group consisting of hydrogen cation type beta zeolite, hydrogen cation type ZSM-5 zeolite, and hydrogen cation type Y zeolite.

2. High silica zeolite is SiO 2 / Al 2 O 3 2. The process for producing an olefin polymer according to claim 1, wherein the molar ratio is from 5 to 40.

3. 3. The process for producing an olefin polymer according to claim 1, wherein the high-silica zeolite is a transition metal-substituted high-silica zeolite.

4. The method for producing an olefin polymer according to any one of claims 1 to 3, characterized in that the polymerization solvent is one obtained by performing slurry polymerization of an olefin in at least one solvent selected from the group consisting of pentane, hexane, heptane, octane, decane, cyclopentane, cyclohexane and methylcyclopentane in the presence of a solid catalyst containing at least titanium, magnesium and a halogen.

5. 5. The process for producing an olefin polymer according to claim 1, wherein the olefin is at least one selected from the group consisting of ethylene, propylene, butene-1, hexene-1 and octene-1.

6. The method for producing an olefin polymer according to any one of claims 1 to 5, wherein the high-silica zeolite is in the form of pellets and further contains at least one binder selected from the group consisting of silica, alumina, silica-alumina and clay.

Citation Information

Patent Citations

  • JP1963-002387B

  • Purification of solvent

    JP1980151003A

  • Liquid phase epitaxially growing method and device therefor

    JP1982056924A

  • Magnet fastner

    JP1989058202A

  • Monolithic concrete execution work device and monolithic concrete execution method

    JP1994017405A